2008
DOI: 10.1093/ndt/gfn545
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation and anti-inflammation by haem oxygenase-1 contribute to protection by tetramethylpyrazine against gentamicin-induced apoptosis in murine renal tubular cells

Abstract: Collectively, we suggest that HO-1 induced by TMP might, at least in part, protect against gentamicin-induced nephrotoxicity through antiapoptotic and anti-inflammatory mechanisms, and that it may have therapeutic potential for patients with renal disease. This is also the first demonstration that HO-1 increases Hax-1 mitochondrial localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 44 publications
4
44
0
2
Order By: Relevance
“…19 Gentamicin-induced kidney damage is characterized by apoptosis, renal tubular epithelial cell necrosis, oxidative stress, inflammatory responses, and vascular contraction. 20,21 In the present study, we demonstrated the protective effects of edaravone in a gentamicininduced nephrotoxicity model. Additionally, prominent increase in serum creatinine and urea concentration is suggested by a sign of significant impairment of kidney function in gentamicin induced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 60%
“…19 Gentamicin-induced kidney damage is characterized by apoptosis, renal tubular epithelial cell necrosis, oxidative stress, inflammatory responses, and vascular contraction. 20,21 In the present study, we demonstrated the protective effects of edaravone in a gentamicininduced nephrotoxicity model. Additionally, prominent increase in serum creatinine and urea concentration is suggested by a sign of significant impairment of kidney function in gentamicin induced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 60%
“…The severe complications resulting from GM-induced nephropathy are limiting factors for its clinical use (32,33). Gentamicin-induced kidney injury is characterized by renal tubular epithelial cell necrosis, apoptosis, inflammatory responses, oxidative stress, and vascular contraction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…52 Inhibition of NF-B in these circumstances promotes cell death; however, NF-B/RelA activation is involved in the apoptosis of podocytes in HIV-transgenic mice mediated by NF-B-dependent Fas and Fas ligand expression in nephrotoxin and ischemia-induced tubular cell apoptosis. 42,49,53,54 …”
Section: Regulation Of Transcriptionmentioning
confidence: 99%